Unveiling the Impact of Spiritual Intelligence on Social Innovation and Success in Social Enterprises: A Conceptual Exploration - Timothy Andrianus Philemon; Riarni Adina Ardanareswari; Adinda Oktaviani Rachdian (Research Synergy Foundation, 2025)
This study examines how spiritual intelligence (SI) can serve as a catalyst for ethical, culturally rooted social innovation in social enterprises, an area often overlooked in literature dominated by Western, profit-oriented perspectives. Drawing on an integrative review of 63 peer-reviewed works published between 2014 and 2024, the research weaves together theoretical and contextual insights to develop a conceptual model. SI is presented not simply as another form of intelligence, but as a guiding moral compass grounded in transcendence, setting it apart from emotional and social intelligences that primarily focus on interpersonal dynamics. Through dimensions such as consciousness, purpose, serenity, and transcendence, SI equips entrepreneurs to turn deeply held values into tangible, innovative solutions, with purpose acting as a bridge and cultural context shaping outcomes. Indonesia, with traditions like gotong royong and tri hita karana, emerges as a rich setting to observe this phenomenon in practice. The study offers practical pathways, from short-term pilot initiatives such as community co-design workshops to long-term strategies like embedding SI in entrepreneurial education and adapting evaluation metrics to local cultures. While conceptual in scope and limited to English-language literature, the work lays the groundwork for future empirical research using mixed methods across diverse cultural contexts.